Adubação com nitrogênio em cobertura e molibdênio por via foliar na cultura do feijão comum - Rosa, Willian Bosquette (2016)
The objective of this study was to evaluate the effect of the application of nitrogen (N) in coverage and molybdenum (Mo) by foliar application in the common bean (Phaseolus vulgaris L.). Three experiments were conducted in two cities in the western Parana (Toledo and Candido Rondon Rondon-PR) called Toledo, MCR 1st and 2nd harvest. The experiments were conducted at the field level in a randomized block design with four replications in a factorial 5 x 4, five nitrogen dosages (0, 30, 60, 120 and 240 kg ha-1) and four molybdenum dosages by leaf (0, 35, 70 and 140 g ha-1). The combinations and repetitions totaling 80 treatments in an area of 2,700 m2. The applications were performed at the phenological stage V4. The experimental plots were composed of 12 seeding rows, spaced 0,5 meters from each other, with five meters in length, featuring an experimental unit of 30 m2. The mass of 1,000 grains increased linearly in the three experiments above 60 kg ha-1 of nitrogen. Dosages of 120 and 240 kg ha-1 compared with 30 kg ha-1 at the Toledo experiment yielded a 12% increase in plant height, and 15% yield. Considering the experiment MCR 2nd harvest, the difference in productivity between the dose of 30 and 240 kg ha-1 of nitrogen is 1306 kg ha-1, an increase of 51%. The productivity of MCR experiments 1st and 2nd harvest were on average 35% higher compared to the experiment of Toledo. Generally, the dose of 140 g ha-1 molybdenum resulted in an increase of 8, 21 and 25% of the productivity experiments Toledo and MCR 1st and 2nd crop, respectively. The significant interactions for nitrogen x molybdenum, a significant effect only for the number of seeds per pod. When bean underwent dosage of 140 g ha-1 of molybdenum and increasing nitrogen rates, the increase in the number of seeds per pod was linear in all experiments. The application of nitrogen in coverage and molybdenum by foliar raised the leaf nitrogen content and crop yield. The economic viability of nitrogen doses, the dose of 120 kg ha-1 was expressed that the best net revenues. In summary, the application of nitrogen and molybdenum in bean crop, adds values in agronomic variables, including productivity, raises the leaf nitrogen content and is economically viable